Answer:
n=6
Step-by-step explanation:
The equation which describes Kurt's problem is:
![n(n+1)+3=45](https://img.qammunity.org/2023/formulas/mathematics/college/6kuet906v71i7ohb863yoe7n6f4kp28co4.png)
We are required to solve for n.
![\begin{gathered} n(n+1)+3=45 \\ n(n+1)=45-3 \\ n^2+n=42 \\ n^2+n-42=0 \end{gathered}](https://img.qammunity.org/2023/formulas/mathematics/college/uv7201dwg5sbxwpr6cybzs5mueku6a4wh8.png)
We then solve the quadratic equation obtained above by factorization.
![\begin{gathered} n^2+7n-6n-42=0 \\ n(n+7)-6(n+7)=0 \\ (n-6)(n+7)=0 \\ \implies n-6=0\lor n+7=0 \\ \implies n=6\lor n=-7 \end{gathered}](https://img.qammunity.org/2023/formulas/mathematics/college/o13vqh3yvfjbghubg89we5r3g7jwirc4o0.png)
Since we are dealing with whole numbers, and -7 is not a whole number, we conclude that -7 is not a valid result.
The number, n which makes the equation true is 6.